Kesaksian Notaris terkait Pemalsuan Surat di Bawah Tangan - Dahlan Dahlan (Kanun Jurnal Ilmu Hukum, 2014)
This paper aims to explore and explain the thoughts regarding theory and concept of witness value witness provided by a notary having registrated and recorded underhand deed which is in fact later alleged to be a crime of signature conterfeiting. This research is also purpused of making investigation fully understand the meaning of the witness the case and it is eligible for the evidence as required by criminal justice procedure law. A Notary Witness in Relation to Underhand Conterfeiting Letter